Respuesta :

1. You have that:

 - The lengths of the bases are (6x-1) units and 3 units.
 - The midsegment has a length of (5x-3) units.

 2. To solve this exercise, you must apply the formula for calculate the length of the midsegment of a trapezoid, which is shown below:

 Midsegment=Base1+Base2/2

 As you can see, the midsegment is half the sum of the bases of the trapezoid.

 3. When you substitute the values, you obtain:

 (5x-3)=[(6x-1)+3]/2

 4. Now, you can solve the problem by clearing the "x":

 (5x-3)=[(6x-1)+3]/2
 2(5x-3)=6x-1+3
 10x-6=6x+2
 10x-6x=2+6
 4x=8
 x=8/4
 x=2
ACCESS MORE